The occurrence and experience of impulsivity and extreme positive mood in a non-clinical sample - Rawlings, Jodie (2012)
The literature has struggled to reach an acceptable definition for the construct of impulsivity. Different models have variously suggested that the crux of the impulsivity construct lies in lack of planning, difficulties in concentration, failure of inhibition or attraction to sensation or immediate reward. More recently, research has suggested that impulsivity is increased in conditions of extreme affect, either positive or negative. The development of a novel measure of affective impulsivity, termed the UPPS-P Impulsive Behaviour Questionnaire, has enabled quantitative investigation of the construct.